Preclinical Investigation of Goniotomy Using Four Different Techniques - Ammar DA (Dove Medical Press, 2020)
David A Ammar,1 Leonard K Seibold,2 Malik Y Kahook2 1Research Department, Lions Eye Institute for Transplant & Research, Tampa, FL, USA; 2Department of Ophthalmology, University of Colorado School of Medicine, Aurora, CO, USACorrespondence: Malik Y KahookUniversity of Colorado School of Medicine, 1675 Aurora Ct, Aurora, CO 80045, USATel +1 720 848 2500Fax +1 720 848 5014Email malik.kahook@cuanschutz.eduPurpose: To evaluate the tissue-level effects of goniotomy techniques on human trabecular meshwork (TM).Design: Laboratory investigation.Methods: The TM from human cadaveric corneal rim tissue was treated using 4 techniques: (1) microvitreoretinal (MVR) blade; (2) 360° trabeculotomy with 5-0 prolene suture; (3) the Kahook Dual Blade (KDB) Glide® device; (4) TrabEx™ device; tissue samples underwent standard histologic processing with H&E stain followed by comparative analyses.Results: The MVR blade exhibited incision of TM extending into the scleral wall. The TrabEx device removed a small portion of TM with large leaflet tissue remnants in all treated areas. 360° suture trabeculotomy resulted in incision of the TM proximate to Schwalbe’s line with no excised tissue evident in all treated areas. Areas treated with the KDB Glide device resulted in nearly complete excision of TM without injury to surrounding tissues.Conclusion: The various methods used for performing goniotomy or trabeculotomy resulted in varying degrees of incision or excision of TM. Only the KDB Glide device resulted in reliable excision of TM with the other devices producing incision or variable excision of tissue. Clinical correlation is required to better understand the implications of the current findings when using these methods to lower intraocular pressure in eyes with glaucoma.Keywords: glaucoma, goniotomy, trabecular meshwork